Grass-dominated stream sites exhibit low fish species diversity and dominance by guppies: an assessment of two tropical pasture river basins - Casatti, Lilian [UNESP]; Ferreira, Cristiane de Paula [UNESP]; Carvalho, Fernando Rogerio (Springer, 2009)
This study investigates whether (1) structural configuration (considering substrate composition, wood debris, marginal and riparian vegetation) of streams suggests habitat simplification on a basin scale and (2) fish assemblage structure follows stream habitat configurations. Ninety-five sites in two pasture basins in southeastern Brazil were randomly selected. Two passes of electro-fishing were done in a 75-m reach at each site. Ten habitat descriptors related to in-stream and riparian physical structures were evaluated at each stream reach. Two groups of streams were identified by principal component analysis: a grassy and a non-grassy group. In comparison to non-grassy sites, grass-dominated streams exhibited a more homogenous fish fauna due to lower species diversity and higher dominance, especially by the guppy Poecilia reticulata, a highly generalist exotic species. The grassy group had not only the most simplified habitat but also the most simplified fish fauna, and the combination of grass-dominated, completely deforested, heavily silted conditions with recent land use conversion may cause a future habitat homogenization followed by a fish fauna homogenization on a regional scale.
Keywords: Habitat structure; Simplification; Riparian vegetation; Non-native species; Poecilia reticulata